Association of dental injuries with maxillofacial fractures: a 10‐year retrospective study. (23rd November 2016) - Ghosh, R.; Gopalkrishnan, K.; Adirajaiah, S.
Abstract: Aim: The aim of the study was to find the prevalence of dental injuries in patients with facial fractures. Materials and methods: A prospective study was conducted of patients who reported in SDM Craniofacial Unit with maxillofacial fractures from January 2003 until December 2013. A total of 991 patients were included in the study. Clinical and radiological examination findings were recorded to evaluate demographics, aetiology, presentation, and type of facial fracture, as well as its relationship with dental injury site and type. Results: Among these 991 patients, 201 patients (41.8%) had associated dental injuries, with a total of 462 injured teeth. Of the 462 injured teeth, 283 (61.2%) were in the maxilla and 179 (38.7%) in the mandible. The central incisor was the most injured tooth for both the maxilla (150, 32.5%) and mandible (80, 17.3%). The most common type of dental injury was avulsion (229, 44.6%). Avulsions were more common in anterior teeth of both maxilla and mandible, whereas in posterior teeth, Ellis Class I fracture or crown fractures were more common. Most vulnerable teeth were maxillary central incisors in the anterior region, whereas in posterior region, first premolars were more prone to injury in the maxillary arch and first molars in the mandibular arch. Conclusion: Our study shows that the occurrence of dental trauma is significantly related to the pattern of injury and site of maxillofacial fractures.